First genome sequence of St. Louis encephalitis virus (SLEV) isolated from a human in Brazil - Vedovello, Danila; Drumond, Betânia Paiva; Marques, Rafael Elias; Ullmann, Leila Sabrina [UNESP]; Fávaro, Eliane Aparecida; Terzian, Ana Carolina Bernardes; Moraes Figueiredo, Luiz Tadeu; Teixeira, Mauro Martins; Araújo Junior, João Pessoa [UNESP]; Nogueira, Mauricio Lacerda (Springer, 2015)
St. Louis encephalitis virus (SLEV), a member of the family Flaviviridae, genus Flavivirus, is a causative agent of encephalitis in the Americas. In Brazil, sporadic cases of SLEV infection have been reported since 1953, but the first outbreak of SLEV in Brazil was identified only in 2007, concomitant with an outbreak of dengue virus (DENV) serotype 3. This finding, along with other reports, indicates that SLEV circulation in Brazil is largely unknown, and there may be epidemiological implications of the co-circulation of SLEV, DENV and other flaviviruses in Brazil. Here, we describe the first complete genome sequence of an SLEV strain isolated from a human patient in Brazil, strain BeH 355964. Phylogenetic analysis was performed to determine the genotype of BeH 355964 using the full-length genome and envelope (E) gene sequences separately. Both analyses showed that BeH 355964 could be classified as genotype V. Although the number of single gene sequences available is greater (such as for the E gene), the phylogenetic tree based on the complete genome sequence was better supported and provided further information about the virus.